Pasas a partir de Physalis angulata (bolsa mullaca) secado en bandejas y con capacidad antioxidante - Arriaran Rodriguez, Leidy Diana (2022)
In the Peruvian Amazon there is a wide variety of fruit tres whose fruit production has not been exploited technologically, such as Physalis angulata (Bolsa mullaca), for this reason this research was to obtain a technology for the production of Physalis angulata raisins using the drying technique in trays with a high antioxidant capacity, the desing was experimental, completely experimental and randomized, with two study factors and three levels respectively; The best producto determined by the different analyzes were the raisins dried at 55°C for 27.5 hours with physicochemical values of 14.34% moisture, 4.37% ash, 1.43% fat, 5.92% protein, 73.94% carbohydrate, 16.77% total fiber, 2.24% acidity, 5.20 pH and suitable for human consumption determined by microbiological análisis and has a shelf life of approximately one year; on the other hand, the antioxidant activity determinated by the DPPH method presented a value of 4,199± 1,844 umolTE/g dry matter, ABTS of 35,039±1,926 umolTE/g dry matter and total phenols of 1,716 (±0,266) mgGAE/g. The technology found can contribute to the development of the región and especially to the producers of this fruit.